2013
DOI: 10.1177/1875974212465573
|View full text |Cite
|
Sign up to set email alerts
|

Urinary retention following transperineal template prostate biopsy – study of risk factors

Abstract: Background: As greater numbers of transperineal template prostate biopsies (TTPBs) are being performed, we have noticed that a considerable number of patients experience urinary retention post-procedure. We wanted to quantify this, and to examine factors that might predict which patients will experience retention. Patients and methods: Data analysis was performed on a prospectively maintained database on 93 consecutive patients undergoing template prostate biopsy over a 12-month period. Results: Mean patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Although TTBP has a higher diagnostic value than conventional 10-core TRUS-guided prostatic biopsies, the average number of core biopsies taken in a mapping TTBP is significantly high and patients are more likely to suffer a degree of pain and discomfort after TTBP [ 41 ]. Besides, the complication of acute urinary retention is reported in about 17% of patients who underwent TTBP [ 42 44 ]. Therefore, it remains controversial whether TTBP can completely replace TRUS-guided biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Although TTBP has a higher diagnostic value than conventional 10-core TRUS-guided prostatic biopsies, the average number of core biopsies taken in a mapping TTBP is significantly high and patients are more likely to suffer a degree of pain and discomfort after TTBP [ 41 ]. Besides, the complication of acute urinary retention is reported in about 17% of patients who underwent TTBP [ 42 44 ]. Therefore, it remains controversial whether TTBP can completely replace TRUS-guided biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly‐observed complication resulting from TPB was AUR, which occurred in 5.5 per cent of patients. Previous research has recorded rates of AUR to be 1.7–39.4 per cent following TPB, compared to 0.2–0.8 per cent for the TRB technique …”
Section: Discussionmentioning
confidence: 90%
“…21 Two studies compared the number of prostate cores taken during TPB between those who developed AUR and those who did not, with neither identifying a significant correlation on multivariate analysis. 18,20 Nevertheless, one study found a significant association, 6 while Buskirk et al recorded the number of needle incursions as the only prognostic factor significant for AUR. 26 These varying analyses, coupled with often a small number of AUR event rates, makes drawing a definitive conclusion to this issue problematic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations